Study on the wave energy capture spectrum based on wave height take-off. (1st July 2022) - Gong, Haoxiang; Cao, Feifei; Han, Zhi; Liu, Shangze; Shi, Hongda
Abstract: With the progress in wave energy research, large-scale development has become a trend. In real sea states, the energy extraction characteristic of each unit is significant to the array's composition. Only focusing on the mean absorbed power for optimization cannot provide guidance for realizing the internal mechanism of the energy capture behavior. Therefore, by extending the concept of Wave Height Take-off (WHTO) to random waves, this paper proposed and defined the Wave Energy Capture Spectrum (WECS), which derives from the change of wave height to describe the energy extraction characteristics of wave energy converters in real sea states. Simulations were conducted in a validated 2D numerical wave flume with a cuboid heaving buoy under different sea states. Linear Power Take-off (PTO) damping coefficient was taken as an example for a parametric study of the WECS. The results verified the concept and showed that the optimization method of WECS can reveal the capture characteristics of the device from both the perspective of frequency and energy. The comparison of capture efficiency between WECS and the conventional PTO method indicated that the difference is not significant, which also examined the method. This manuscript aims to validate the concept and promote the method. Highlights: A new concept of wave energy capture spectrum (WECS) that based on WHTO is proposed. Simulations with cuboid buoy were conducted in random waves to validate the concept. Capture efficiency obtained by WECS and the conventional PTO method were compared.